(untitled) (London Journal of Research In Management & Business, 2024)
The primary responsibility of any country’s government is to enhance the quality of life for its citizens, ensuring they have opportunities to live comfortably. Government actions significantly influence the social, economic, and political stability of a nation. Public servants play a crucial role in implementing these public policies and services. Consequently, the number of public servants is a critical indicator of the accessibility of public services. Numerous studies explore the availability of public services based on a country’s macroeconomic and demographic metrics. We believe that public services should aim to positively impact every citizen’s life, thus improving their quality of life. In this paper, our study intended to examine the availability of government services using social and economic indicators relevant to families and individuals -such as the gross domestic product per capita, the number of government employees per thousand people, and the country’s happiness index. The cluster regression method was utilized for this analysis.